2011
DOI: 10.3168/jds.2010-3834
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Evidence for a major gene by polygene interaction for milk production traits in German Holstein dairy cattle

Abstract: The present study investigated putative interaction effects between the DGAT1 K232A mutation and the polygenic term (i.e., all genes except DGAT1) for 5 milk production traits in the German Holstein dairy cattle population. Mixed models were used, and the test for interaction relied on the comparison of polygenic variance components depending on the sire's genotypes at DGAT1 K232A. Substitution effects were highly significant for all traits. Significant interaction effects were found for milk fat and protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
2
11
1
Order By: Relevance
“…When the least square mean of the traits was considered (Table 2), genotype KK gives the most effect on milk composition content traits, while genotype AA has the most effect on milk yield and milk composition yield traits. This result was in accordance with the studies of Cardoso et al (2011), Streit et al (2011, Barbosa et al (2010), Banos et al (2008), Bennewitz et al (2004), Gautier et al (2007), Grisart et al (2002), Kuehn et al (2007), Spelman et al (2002), Thaller et al (2003), and Weller et al (2003) that found that this locus, particularly the KK genotype, has the effect of increasing fat content. These results suggest that the effect of the DGAT1 gene does not only affect milk fat content but also affects the milk composition, particularly, milk protein.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…When the least square mean of the traits was considered (Table 2), genotype KK gives the most effect on milk composition content traits, while genotype AA has the most effect on milk yield and milk composition yield traits. This result was in accordance with the studies of Cardoso et al (2011), Streit et al (2011, Barbosa et al (2010), Banos et al (2008), Bennewitz et al (2004), Gautier et al (2007), Grisart et al (2002), Kuehn et al (2007), Spelman et al (2002), Thaller et al (2003), and Weller et al (2003) that found that this locus, particularly the KK genotype, has the effect of increasing fat content. These results suggest that the effect of the DGAT1 gene does not only affect milk fat content but also affects the milk composition, particularly, milk protein.…”
Section: Resultssupporting
confidence: 94%
“…These results contrast with the study of Schennink et al (2007) and Sun et al (2009). While the studies of Cardoso et al (2011) and Streit et al (2011) found that the K allele of the DGAT1 gene showed a significant association with milk production. Although the results from many studies are inconclusive, it is clear that the DGAT1 gene has a strong association with milk production and milk composition traits.…”
Section: Introductioncontrasting
confidence: 80%
“…Pryce et al (2010) found more than 70 significant SNP effects on BTA14 that included the DGAT1 gene for milk production in dairy cattle (Grisart et al, 2002;Thaller et al, 2003). Streit et al (2011) investigated a major gene (DGAT1) by polygene interaction in German Holsteins and found that the interaction for milk yield was not significant although the interactions for fat percentage and protein percentage were significant. In BTA14, SNP variances for POORP, REPRO, DD, and MAST explained more than 1% of the total additive genetic variance in large NE herds.…”
Section: Snp Marker Estimatesmentioning
confidence: 96%
“…Bernabucci et al [ 5 ] concluded that the sampling station affects total protein concentration and acidity in milk, ranging from 3.2% to 6.0% and from 2.0% to 5.6%, respectively. Moreover, Streit et al [ 6 ] documented the importance of determining the alleles in the diacylglycerol O-acyltransferase 1 genotype in German Holstein sires to avoid differences that can be as high as 20% in the association of these alleles with milk production values as a result of the allele substitution effect.…”
Section: Introductionmentioning
confidence: 99%